Investigating pedestrian safety solutions on rural high-order roads. Case-study: R71 Polokwane - Mokoma, Lesedi Dibuseng (Department of Civil Engineering, 2017)
South Africa's pedestrian accident rate is one of the highest in the world. The percentage of pedestrian accidents to total road accidents is approximately 33% (RTMC, 2011) far greater than the world average of 22% (World Health Organisation, 2013). The problem is more acute in rural areas where 1 in 3 pedestrian accidents results in pedestrian fatalities. The ratio on urban roads is 1 in 10. The sobering pedestrian safety statistics describing South Africa's rural roads have prompted the need to research functional and effective traffic engineering solutions that can improve pedestrian safety on rural high order roads located near human settlements. This investigation is conducted using the R71 Polokwane -a road with a history of pedestrian safety problems- as a case study. Pedestrian safety risk factors and an assessment methodology for pedestrian risk on rural high order roads are derived from a review of local and international literature. The pedestrian risk assessment methodology is applied to the R71 study area. This process highlights the shortcomings of the current accident data collection process. Critical information such as accident cause and location; driver and pedestrian characteristics such as age and gender; important information such as vehicle type and age, injuries, fatalities, etc. are not recorded. The limited data minimises the depth of the analysis however a reasonable high level understanding of the pedestrian safety risk factors and the risk in the study area is attained. The R71 study area is characterised by villages, farms and an urban settlement. The prevalence of pedestrian accidents is higher in villages and lowest in the urban settlements. This is attributed to the infrastructure provision in the urban settlement. The causes of pedestrian risk on the R71 are concluded as: ● Lack of integrated land use and transport planning; ● Lack of pedestrian infrastructure. ● Poor design of speed transition zones between rural areas and villages and urban areas. A literature review of effective pedestrian safety measures that are being implemented locally and abroad is compiled. Some of the solutions are impractical for the rural South African context particularly because they are dependent on consistent energy sources and may require routine maintenance. A solution framework based on the pedestrian safety risk identified on the R71 is designed to guide countermeasure selection and design in rural contexts. In the end, solutions deemed suitable for the rural context are: effective high to low speed transition zones; the provision of fenced-off service roads and strategic crossing points; and the removal and enforcement of land use in the road reserve of high order roads. These solutions must be complemented with community training and consistent law enforcement.